2021
DOI: 10.1002/etc.5011
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Responses of Palladium Accumulation in Duckweed (Lemna minor): Determination of Biomarkers

Abstract: Palladium (Pd) is a trace metal of the platinum group elements, representing an emerging contaminant for the environment. It is of great interest to characterize the bioaccumulation and toxicity of Pd to improve our toxicological knowledge for this contaminant. Under standardized toxicity testing conditions, we analyzed Pd accumulation and toxicity effects on the duckweed Lemna minor exposed to nominal concentrations from 2 to 50 µM. The inhibitory effect was significant (p < 0.05) from 8 µM of Pd, starting wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…BW9 soil elutriate sample could affect the photosynthetic process of L. minor, possibly due to PTE concentrations recorded [Al (0.222-0.365 mg/ L), Mn (0.05-0.09 mg/L), Ni (0.007-0.011 mg/L), Zn (0.04-0.05 mg/ L)] that could be incorporated in the chlorophyll molecule during the process. Indeed, the excess PTE accumulated could be used in this pigment biosynthesis, altering its functional property (Jmii and Dewez, 2021). Hou et al (2007) already showed that total chlorophyll decreases in L. minor with the increase of PTE concentration (Cu > 10 mg/L; Cd > 0.5 mg/L), due to the peroxidation of chloroplast membranes mediated or replacing Mg in chlorophyll molecules by PTE.…”
Section: Lemna Minormentioning
confidence: 99%
“…BW9 soil elutriate sample could affect the photosynthetic process of L. minor, possibly due to PTE concentrations recorded [Al (0.222-0.365 mg/ L), Mn (0.05-0.09 mg/L), Ni (0.007-0.011 mg/L), Zn (0.04-0.05 mg/ L)] that could be incorporated in the chlorophyll molecule during the process. Indeed, the excess PTE accumulated could be used in this pigment biosynthesis, altering its functional property (Jmii and Dewez, 2021). Hou et al (2007) already showed that total chlorophyll decreases in L. minor with the increase of PTE concentration (Cu > 10 mg/L; Cd > 0.5 mg/L), due to the peroxidation of chloroplast membranes mediated or replacing Mg in chlorophyll molecules by PTE.…”
Section: Lemna Minormentioning
confidence: 99%
“…Respond to subcellular biochemical, immunological and genetic changes (DNA modifications) with no visible morphological and physiological changes (Dunham et al, 2019;Jmii and Dewez, 2021;Jaskulak and Grobelak, 2019) Reaction biomarkers Physiognomic degree of damage depending on the acting factor physiological reaction of plants to the action of the given factor shows in functional disorders such as restricted flowering, dieback of some organs, reduction of overall life or limitation of the most important life processes (Fränzle, 2006;Khalid et al, 2019;Veskoukis et al, 2019;Martínez and Barrera, 2021).…”
Section: S2mentioning
confidence: 99%